2014
DOI: 10.1088/1468-6996/15/5/055005
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and doping mechanism of theranostic Eu3+/Fe3+dual-doped hydroxyapatite nanoparticles

Abstract: Theranostic nanoparticles currently have been regarded as an emerging concept of ‘personalized medicine’ with diagnostic and therapeutic dual-functions. Eu3+ doped hydroxyapatite (HAp) has been regarded as a promising fluorescent probe for in vivo imaging applications. Additionally, substitution of Ca2+ with Fe3+ in HAp crystal may endow the capability of producing heat upon exposure to a magnetic field. Here we report a preliminary study of doping mechanism and photoluminescence of Eu3+ and Fe3+ doped HAp nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 50 publications
3
26
1
Order By: Relevance
“…Synthesized powders and consolidated samples were characterized by various methods, including X-ray diffraction (XRD), Raman spectroscopy, high-resolution transmission electron microscopy (HR-TEM), and Vickers indentation technique. So far, a lot of research has been done on the applications of HA and graphene materials in the field of theranostics, which confirms the capabilities of these materials in this field [46][47][48][49][50][51]. Given that each phase of the nanocomposite has the potential to be used in biomaterials and theranostics, the synthesized nanocomposite is expected to be usable in biological and theranostic applications.…”
Section: Introductionmentioning
confidence: 71%
“…Synthesized powders and consolidated samples were characterized by various methods, including X-ray diffraction (XRD), Raman spectroscopy, high-resolution transmission electron microscopy (HR-TEM), and Vickers indentation technique. So far, a lot of research has been done on the applications of HA and graphene materials in the field of theranostics, which confirms the capabilities of these materials in this field [46][47][48][49][50][51]. Given that each phase of the nanocomposite has the potential to be used in biomaterials and theranostics, the synthesized nanocomposite is expected to be usable in biological and theranostic applications.…”
Section: Introductionmentioning
confidence: 71%
“…The easier synthesis method that we propose allows us to obtain hydroxyapatite nanoparticles with a size and shape that are more suitable for biomedical applications (the cellular uptake requires sizes under 70 nm and spherical shape) [16]. …”
Section: Resultsmentioning
confidence: 99%
“…Although some europium-doped hydroxyapatite nanoparticles have been reported, these materials have not been really tested against oral fibroblasts (HGF-1) and HeLa cells and as chemotherapy drugs release systems to demonstrate their potential application. Chen et al reported the synthesis of theranostic Eu 3+ /Fe 3+ dual-doped hydroxyapatite nanoparticles without a high temperature calcination and with excellent fluorescent properties but they did not test these particles against oral cells [16]. …”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectra of HAp and doped samples were shown in Fig.2. The spectrum was recorded in the region of 4000 cm -1 -400 cm -1 .Thevibrational mode ν 4 of (PO 4 ) 3was obtained at 567 cm -1 , 603 cm -1 and 633 cm -1 which correspondsto hydroxyapatite [13]. The O-H band was observed at 3427 cm -1 due to the presence of H 2 O molecules.…”
Section: Ftir Analysismentioning
confidence: 99%